Pathogenetic mechanisms of ischemic stroke: from verification to secondary prevention - Aleksey A. Kulesh; Dmitrii A. Demin; Oleg I. Vinogradov (ZAO "Consilium Medicum", 2021)
Ischemic stroke is an extremely heterogeneous disease: there are more than 200 causes of cerebral catastrophe. Early identification of the pathogenetic mechanism (subtype) of ischemic stroke allows planning an individual secondary prevention strategy, which includes a wide range of pharmaceutical and surgical methods. The article presents the characteristics of cardioembolic (associated with atrial fibrillation and flutter, prosthetic valves, chronic heart failure, left ventricle thrombus, infective endocarditis, open foramen ovale, etc.), atherothrombotic (due to extra- and intracranial atherosclerosis), lacunar and cryptogenic stroke, as well as less common causes of the disease, in particular cervical or cerebral artery dissection. Issues of secondary prevention of stroke according to the pathogenetic subtype are described and summarized as an algorithm. The article is illustrated with clinical examples.